Variation of Functional Neurological Symptoms and Emotion Regulation with Time - Kienle, Johanna; Rockstroh, Brigitte; Fiess, Johanna; Schmidt, Roger; Popov, Tzvetan; Steffen-Klatt, Astrid (Frontiers in Psychiatry, 2018)
Introduction: The present study addressed the variation of emotion regulation in the context of functional neurological symptom disorder (FNSD) by examining changes of functional neurological symptoms (FNS), general psychological strain, alexithymia, emotion regulation strategies and cortical correlates of emotion regulation in the context of a standard inpatient treatment program. Methods and Materials: Self-report data on functional neurological symptoms, general psychological strain, alexithymia, emotion regulation strategies and cortical correlates of an experimentally induced emotion regulation task (participants either passively watched unpleasant and neutral pictures or regulated their emotional response to unpleasant pictures using pre-trained reappraisal, while an electroencephalogram was recorded) were compared between 19 patients with FNSD and 19 healthy comparison participants (HC) before and after a four-week standard treatment protocol that included a combination of (individual and group) psychotherapies and functional treatments (such as physiotherapy) or a four-week interval in HC respectively. Results: General psychological strain did not decrease significantly in FNSD patients. Changes in emotion regulation in FNSD patients were constrained to an increase in self-reported use of cognitive reappraisal strategies. Subjective symptom intensity in FNSD patients varied with alexithymia pre-treatment, but did not decrease significantly. Cortical activity in the time and frequency domain distinguished passive watching of neutral and unpleasant pictures, and regulating emotional responses upon unpleasant pictures from passively watching them without difference between groups and/or time. Discussion: Over the investigated time interval, augmented habitual cognitive emotion regulation suggests an alleviation of emotion processing deficits, but no significant symptom decrease. More controlled and prolonged treatment studies would be needed to determine whether and how a specific contribution of treatment-related changes of emotion regulation and functional neurological symptoms might be inferred